DEVELOPMENT OF ETHNO-STEM BASED MODULES INTEGRATED WITH CREATIVE THINKING ON ELEMENTS, COMPOUNDS AND MIXTURES MATERIAL - Lubis, Erina Debora Mastauli; Djulia, Ely; Samdinal, Samdinal (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
The limited relevance of science learning and the dominance of conventional teaching methods have led to low creative thinking skills among students. This study aims to develop an Ethno-STEM-based module integrated with creative thinking skills on the topic of elements, compounds, and mixtures. The development model used is the 4D model (Define, Design, Develop, and Disseminate), limited to expert validation, teacher and student responses. The module integrates local wisdom and cultural contexts with STEM learning stages, fostering fluency, flexibility, originality, and elaboration. The validation results show that the module meets the "very valid" criteria from material experts (Aiken’s V = 0.85), learning experts (0.84), media experts (0.81), and test instrument validators (0.83). Science teachers also rated the module very valid (0.89). Student responses reached an average of 89%, categorized as “very practical,” indicating that the module is attractive, easy to understand, culturally relevant, and effective in stimulating creative thinking. Thus, the developed Ethno-STEM module is highly feasible, practical, and relevant as an alternative teaching material in supporting the Independent Curriculum and enhancing students’ creative thinking. ABSTRAK Keterbatasan relevansi pembelajaran sains dan dominasi metode pengajaran konvensional telah menyebabkan rendahnya kemampuan berpikir kreatif di kalangan siswa. Studi ini bertujuan untuk mengembangkan modul berbasis Etno-STEM yang terintegrasi dengan kemampuan berpikir kreatif pada topik unsur, senyawa, dan campuran. Model pengembangan yang digunakan adalah model 4D (Definisikan, Rancang, Kembangkan, dan Sebarkan), yang dibatasi oleh validasi ahli, Guru dan respons siswa. Modul ini mengintegrasikan kearifan lokal dan konteks budaya dengan tahapan pembelajaran STEM, mendorong kelancaran, fleksibilitas, orisinalitas, dan elaborasi. Hasil validasi menunjukkan bahwa modul tersebut memenuhi kriteria "sangat valid" dari para ahli materi (Aiken’s V = 0,85), ahli pembelajaran (0,84), ahli media (0,81), dan validator instrumen tes (0,83). Guru IPA juga menilai modul tersebut sangat valid (0,89). Respons siswa mencapai rata-rata 89%, dikategorikan sebagai "sangat praktis," menunjukkan bahwa modul tersebut menarik, mudah dipahami, relevan secara budaya, dan efektif dalam merangsang berpikir kreatif. Dengan demikian, modul Ethno-STEM yang dikembangkan sangat layak, praktis, dan relevan sebagai bahan ajar alternatif dalam mendukung Kurikulum Mandiri dan meningkatkan pemikiran kreatif siswa.